2021
DOI: 10.1007/978-3-030-74608-7_61
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety and Health Education and Training: A Latent Dirichlet Allocation Systematic Literature Review

Abstract: Education and training play an increasingly meaningful role in recent research on Occupational Safety and Health (OSH) through the whole companies' supply chains. However, considering the extent of the subject, most research works focus on specific issues, which are not easily replicable in other contexts. Therefore, this work gathers the main results achieved by researchers and systematically identifies leading research paths and trends for future works. A review and systematic categorisation of the existent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…All these topics were consistent with other topic modelling studies on training materials (e.g. Micheli et al, 2021 ). While these results point to the strengths of these manuals, the present study’s examination also encountered some problematic aspects of this training discourse.…”
Section: Discussionsupporting
confidence: 90%
“…All these topics were consistent with other topic modelling studies on training materials (e.g. Micheli et al, 2021 ). While these results point to the strengths of these manuals, the present study’s examination also encountered some problematic aspects of this training discourse.…”
Section: Discussionsupporting
confidence: 90%
“…technologies and education [21]. Michelli et al [22] identified and analyzed the key factors affecting the success of OHS trainings in companies.…”
Section: Shortmentioning
confidence: 99%